2021
DOI: 10.1021/acscatal.1c02731
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and Theory of Bimetallic Pd-Catalyzed α-Arylation and Annulation for Naphthalene Synthesis

Abstract: We report the synthesis of bimetallic Pd­(I) and Pd­(II) complexes with bidentate 2-phosphinoimidazole ligands and their catalytic activity to generate substituted naphthalenes. This process involves the coupling of an aryl iodide and 2 equiv of a ketone via sequential ketone α-arylation and then annulation to generate disubstituted and tetrasubstituted naphthalenes in a regioselective manner. Excellent substrate scope for both aryl iodide and ketone partners is demonstrated, including that for heteroaryl iodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 61 publications
2
21
0
Order By: Relevance
“…We previously reported the catalytic activity of bimetallic complexes 1 and 2 in a newly discovered naphthalene synthesis reaction that occurs via tandem ketone arylation and cyclization . In that study, we found that Pd­(II) complex 2 had slightly higher reactivity than the Pd­(I) complex.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…We previously reported the catalytic activity of bimetallic complexes 1 and 2 in a newly discovered naphthalene synthesis reaction that occurs via tandem ketone arylation and cyclization . In that study, we found that Pd­(II) complex 2 had slightly higher reactivity than the Pd­(I) complex.…”
supporting
confidence: 91%
“…We recently reported the synthesis of new bimetallic palladium complexes scaffolded on a 2-phosphinoimidazole ligand that can be isolated at either the Pd­(I) or Pd­(II) oxidation states (Figure b) . Mechanistic experiments and DFT calculations confirmed the thermodynamic stability of the dimeric Pd complex with respect to the monomeric form and suggested that the Pd complex stays intact during catalysis.…”
mentioning
confidence: 99%
“…In the context of C–C coupling catalysis, only a few examples with a postulated bimetallic mechanism are known, and little mechanistic detail has been revealed. 19–22 Recently, bimetallic Pd I and Pd II complexes supported by bridging 2-phosphinoimidazole ligands were identified as active catalysts for α-arylation to give naphthalene derivatives. 22 Computations supported a bimetallic mechanism with redox cycling between Pd II and Pd III or Pd IV and Ar–I oxidative addition occurred at a single Pd atom within the bimetallic framework.…”
Section: Introductionmentioning
confidence: 99%
“…19–22 Recently, bimetallic Pd I and Pd II complexes supported by bridging 2-phosphinoimidazole ligands were identified as active catalysts for α-arylation to give naphthalene derivatives. 22 Computations supported a bimetallic mechanism with redox cycling between Pd II and Pd III or Pd IV and Ar–I oxidative addition occurred at a single Pd atom within the bimetallic framework. Of note, similar higher valent Pd II /Pd III or Pd II /Pd IV bimetallic catalytic routes are established for C–X 23 or C–C 24,25 bond formations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation